The Mitochondrial Pentatricopeptide Repeat Protein PPR18 Is Required for the cis-Splicing of nad4 Intron 1 and Essential to Seed Development in Maize - Liu, Rui (Int J Mol Sci, 2020)
Pentatricopeptide repeat (PPR) protein comprises a large family, participating in various aspects of organellar RNA metabolism in land plants. There are approximately 600 PPR proteins in maize, but the functions of many PPR proteins remain unknown. In this study, we defined the function of PPR18 in the cis-splicing of nad4 intron 1 in mitochondria and seed development in maize. Loss function of PPR18 seriously impairs embryo and endosperm development, resulting in the empty pericarp (emp) phenotype in maize. PPR18 encodes a mitochondrion-targeted P-type PPR protein with 18 PPR motifs. Transcripts analysis indicated that the splicing of nad4 intron 1 is impaired in the ppr18 mutant, resulting in the absence of nad4 transcript, leading to severely reduced assembly and activity of mitochondrial complex I and dramatically reduced respiration rate. These results demonstrate that PPR18 is required for the cis-splicing of nad4 intron 1 in mitochondria, and critical to complex I assembly and seed development in maize.